Contextual Design of Literacy and Numeracy–Based Assessments: A Systematic Literature Review - Mursyidah J Parandrengi; Duano Sapta Nusantara; Rohati Rohati; Da Tien Nguyen; Kgaladi Maphutha (Journal of General Education and Humanities, 2026)
The increasing emphasis on literacy and numeracy requires assessment tasks that reflect real-world contexts. However, existing studies indicate that contextual assessment is often implemented at a superficial level, with limited use of second-order contextualization that supports deeper reasoning. This study aims to systematically examine how context is used in the design of literacy and numeracy-based assessments. This research employs a Systematic Literature Review (SLR) of 17 articles published between 2015 and 2025. Bibliometric analysis using VOSviewer and content analysis were conducted to examine context types, context levels (zero, first, and second order), and question design. The findings show that most studies apply context at the zero and first-order levels, while only a few reached second-order contextualization. Context use is dominated by local settings, with contexts such as tourism remaining underexplored. In addition, digital technology is mostly used in non-interactive formats. This study recommends developing PISA-based questions in tourism contexts at the second-order level, as well as integrating interactive digital technology to enhance students’ abilities to formulate, employ, and interpret. This study contributes theoretically by linking context type, context level, and cognitive processes within mathematical literacy frameworks, and practically by guiding the design of more authentic assessment tasks.